Quantitative study on contribution of dynamic imbibition to oil production during fracturing and huff-n-puff in tight reservoirs - Hongxian LIU; Lei BAI; Qiang LUO; Tongjing LIU; Jiangfei SUN; Jiaxing LIU (Shiyou shiyan dizhi)
Fracturing and huff-n-puff in tight reservoirs is a dynamic imbibition process, where crude oil recovery is enhanced mainly through two mechanisms: differential pressure displacement and spontaneous imbibition. However, the contribution rate of these two mechanisms to the quantification of overall oil recovery remains unclear. To address this, a quantitative analysis was conducted on the contribution of dynamic imbibition mechanisms during fracturing and huff-n-puff oil recovery in tight conglomerate reservoirs. Laboratory physical simulation experiments were carried out using natural tight conglomerate reservoir cores, utilizing a high-temperature and high-pressure multi-functional core displacement system and a high-temperature and high-pressure online displacement nuclear magnetic resonance imaging system. Firstly, experiments were conducted on the imbibition characteristics of different types of fracturing oil displacement agents, and the agents with superior imbibition effects were screened out. Secondly, based on evaluations of fracturing and huff-n-puff oil recovery, the most effective fracturing oil displacement agent was identified. Finally, through analyzing factors influencing oil recovery, a quantitative assessment of the production enhancement mechanisms of dynamic imbibition in fracturing and huff-n-puff oil recovery was carried out. The experimental results showed that both surfactants and flow control agents exhibited strong imbibition effects, with flow control agents more effective in enhancing fracturing and huff-n-puff oil recovery. Furthermore, the contribution of imbibition and displacement on oil recovery during the dynamic imbibition process showed opposite patterns. The main research conclusions are as follows. Imbibition dominates as the primary oil recovery mechanism when the fracturing oil displacement agent exhibits a strong ability to reduce interfacial tension and alter wettability. Otherwise, displacement becomes the dominant mechanism. Both surfactants and flow control agents demonstrate good imbibition performance. However, surfactants are less sensitive to huff-n-puff cycles, while flow control agents are more sensitive. Shut-in time is the key factor affecting the contribution rate of imbibition or displacement. However, the contribution rate of displacement remains consistently higher than that of imbibition.